The role of short-term accommodations on the place brand and real estate development of urban areas: A case study of Malate, Manila - Virgilio Angelo Gelera Gener (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: This research looks into how vacation rentals have impacted the image of Philippine cities and the growth of the real estate market there. Through a combination of surveys, in-depth interviews, and focus groups, this study seeks to understand how stakeholders perceive these accommodations regarding their impact on a community’s place brand and land value. Methodology: In this study, we used qualitative methods. Employees and officials of certain developers and identified government offices were interviewed for this study. Findings: The survey found that despite being categorized as "traveler lodgings" in a local tourism circular, most respondents used short-term accommodations for private occasions. That said, respondents still consider the short-term accommodation industry an essential economic player in society, even though it is associated with a negative place brand. At the same time, results from the Pearson Chi-square Test show that 14 out of 17 factors significantly affect respondents’ opinions. When controlling for factors like education and employment, the MLR results show that being born in Malate and part of a family household was the most significant. According to interviews with city officials, short-term accommodations are treated the same as any other type of hotel under the city’s zoning ordinance. Therefore, despite their current association with various sexual activities, it is entirely legal for these establishments to locate themselves near residential areas and/or institutional structures. Finally, residential real estate developers have stated that they have no objections to such dwellings, as the selection of sites for their projects has always been driven solely by suitability, zoning, and marketability. Implications/Novel Contribution: These results call for stricter regulations on sexually suggestive roadside advertising and a recalculation of the local zoning ordinance and tourism circular. After appropriate measures have been refined for implementation, they can open the door for spatial interventions (such as visual buffer corridors) to better meet the needs of locals, private groups, and the government.